2003
DOI: 10.1103/physreve.68.047104
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior of helical cellular automata

Abstract: A helical cellular automata (HCA) model constructed on a two-dimensional grid of cells with a helical structure is presented and the pattern formation of this model studied by numerous computer simulations. It is found that the evolutions of the HCA are sensitive to the circumference of the helix p. With various p, the initial growth of the model generates various patterns ranging from Sierpinski triangle gasket, complex textured pattern, to lateral quasiperiodic structure. A sudden transition from regular fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In particular, all these works assume energy equipartition and consequently, the partial temperatures T i are made equal to the global granular temperature T . However, the failure of energy equipartition in granular fluids [11,12,13,14,15] has also been confirmed by computer simulations [16,17,18,19,20,21,22] and even observed in recent experiments [23,24]. As a consequence, previous studies for granular mixtures based on a single temperature must be reexamined by theories which take into account the effect of temperature differences on the transport coefficients.…”
Section: Introductionmentioning
confidence: 75%
“…In particular, all these works assume energy equipartition and consequently, the partial temperatures T i are made equal to the global granular temperature T . However, the failure of energy equipartition in granular fluids [11,12,13,14,15] has also been confirmed by computer simulations [16,17,18,19,20,21,22] and even observed in recent experiments [23,24]. As a consequence, previous studies for granular mixtures based on a single temperature must be reexamined by theories which take into account the effect of temperature differences on the transport coefficients.…”
Section: Introductionmentioning
confidence: 75%
“…An increase of chain size beyond a critical length, compactification due to interparticle magnetic interactions, formation of globules as nuclei for new dense phase, are all seen in the scheme of phase transitions leading to formation of bulk drop-like aggregates. As to the role of polydispersity, Wang and Holm [19] found that the fraction of large particles, with larger relative dipole moments in proportion to their volume, would overcome thermal forces more easily and respond to weaker fields and therefore dictate magnetization properties (e.g. initial susceptibility), even in case of dilute fluids.…”
Section: Field-induced Aggregates In Non-ideal Ferrofluidsmentioning
confidence: 99%
“…As well known, waveguides are very important devices in photonics, along which photons are transported to carry information. Cavities coupled with waveguides are usually designed to control the transport of light, forming traps, filters, and switches [43][44][45][46][47][48][49][50][51]. The emergence of PTIs provides just right chances to realize reflection-free photonic topological waveguides (PTWs) using photonic topological edge states (PTESs).…”
Section: Introductionmentioning
confidence: 99%